2023
DOI: 10.1101/2023.04.06.535963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of hexanal treatment on fruit qualities and antioxidant activities on ‘Umran’ Indian jujube fruit during cold storage

Abstract: ′Umran′ Indian jujube is a widely grown cultivar due to its marketable quality and productivity, resulting in excellent market value. Despite its high quality, the product′s short shelf life poses a challenge for transportation, even within the domestic market. Hexanal with three concentrations (0.15%, 0.20%, and 0.25%) was applied to the fruit of ′Umran′ Indian jujube at both pit hardening and color break stages. Harvested fruits were stored for 28 days in a cold chamber of 7.5±1°C and 90-95% RH. The changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
4
0
0
Order By: Relevance
“…The findings of the present study are in accordance with those reported by Kaur et al (2019) and Sharma et al (2023), who demonstrated that EFF suppressed the PPO enzyme activity in oriental sweet melons, grape berries and jujube fruit, respectively. PPO is a terminal oxidase that utilizes polyphenols as substrates, which leads to internal browning of fruit.…”
Section: Polyphenol Oxidase Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of the present study are in accordance with those reported by Kaur et al (2019) and Sharma et al (2023), who demonstrated that EFF suppressed the PPO enzyme activity in oriental sweet melons, grape berries and jujube fruit, respectively. PPO is a terminal oxidase that utilizes polyphenols as substrates, which leads to internal browning of fruit.…”
Section: Polyphenol Oxidase Activitysupporting
confidence: 93%
“…These findings indicate that EFF treatment application effectively retained AA content throughout the storage period. Our results corroborate those reported by Cheema et al (2014), Gill et al (2016), Jincy et al (2017), Silué et al (2022) and Sharma et al (2023) who illustrated that EFF retained ascorbic acid of tomato, guava, mango and jujube fruit, respectively. The maturity stage had a significant effect (p < 0.001) on AA content (Figure 1F), with M2 (3.53 mg g −1 FW) exhibiting a greater AA content than M1 (2.54 mg g −1 FW).…”
Section: Ascorbic Acidsupporting
confidence: 93%
See 1 more Smart Citation
“…Results obtained from this study demonstrated that EFF-treated kiwifruit had substantially higher TPC and TFC during storage. The findings attained are in alignment to those reported by Gill et al (2016), Sharma et al (2023), and Öz et al (2023), who demonstrated that EFF effectively maintained higher phenolic content of guava, jujube and persimmon fruit, respectively. Secondary metabolites such as phenolic and flavonoid compounds are crucial for the maintenance of fruit quality, as they delay senescence induced by oxidative degradation, by functioning as antioxidants that scavenge free radicals (Gulcin, 2020).…”
Section: Total Phenolic and Flavonoid Contentsupporting
confidence: 90%